2006
DOI: 10.5642/aliso.20062201.05
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Data in Monocot Phylologenetics

Abstract: Mitochondrial sequences are an important source of data in animal phylogenetics, equivalent in importance to plastid sequences in plants. However, in recent years plant systematists have begun exploring the mitochondrial genome as a source of phylogenetically useful characters. The plant mitochondrial genome is renowned for its variability in size, structure, and gene organization, but this need not be of concern for the application of sequence data in phylogenetics. However, the incorporation of reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 88 publications
6
51
0
2
Order By: Relevance
“…Therefore, as long as the results of combined analysis with genes from all three genomes appear to be improvements over their predecessors, this route should continue to be followed. However, performing combined analyses should not prevent us from exploring the patterns produced by the individual compartments or the potential causes of deviations in pattern, as in Petersen et al (2006). It is also clear that there are problems with the mitochondrial and nuclear genes as indicators of relationships for the achlorophyllous taxa (Burmanniaceae, Corsiaceae, and Triuridaceae) plus Trithuria (Hydatellaceae), the last of which is photosynthetic but which has also been problematic in other studies (Bremer 2002;Davis et al 2004).…”
Section: All Three Genames Versus Plastid Onlymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, as long as the results of combined analysis with genes from all three genomes appear to be improvements over their predecessors, this route should continue to be followed. However, performing combined analyses should not prevent us from exploring the patterns produced by the individual compartments or the potential causes of deviations in pattern, as in Petersen et al (2006). It is also clear that there are problems with the mitochondrial and nuclear genes as indicators of relationships for the achlorophyllous taxa (Burmanniaceae, Corsiaceae, and Triuridaceae) plus Trithuria (Hydatellaceae), the last of which is photosynthetic but which has also been problematic in other studies (Bremer 2002;Davis et al 2004).…”
Section: All Three Genames Versus Plastid Onlymentioning
confidence: 99%
“…Previous studies have demonstrated that although incongruence-as measured by, e.g., the partition homogeneity test-is present, direct combination provides greater resolution and higher bootstrap percentages Reeves et al 2001). We will not address these issues in depth here, but Petersen et al (2006) do examine this question with respect to the two mitochondrial genes, atp 1 and cob. Davis et al (2004) also discussed these issues with respect to atp 1 and rbcL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in Fay et al (2000), representatives of Commelinales, Liliales, Pandanales, and Zingiberales were included as outgroups. For the most part, voucher information for the taxa used in these analyses was previously published (Table 1, Fay et al 2000; or will be published in forthcoming articles (see also Chase et al 2006;Petersen et al 2006).…”
Section: Plant Materialsmentioning
confidence: 99%
“…GenBank numbers for rbcL, atpB, and trnL-F have been previously published Pireset al 2004). GenBank numbers for matK, ndhF, and atp1 are in press or will be presented in forthcoming publications and will not be provided here (see Davis et al 2004;Chase et al 2006;Givnish et al 2006;Petersen et al 2006). This analysis focuses on only 79 taxa of Asparagales and outgroups, but we are preparing a future analysis of ca.…”
Section: Dna Extraction Gene Amplification Sequencing and Alignmentmentioning
confidence: 99%